2013
DOI: 10.1155/2013/461478
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Potential of Chestnut Bee Pollen on Carbon Tetrachloride-Induced Hepatic Damages in Rats

Abstract: Bee pollen has been used as an apitherapy agent for several centuries to treat burns, wounds, gastrointestinal disorders, and various other diseases. The aim of our study was to investigate the hepatoprotective effects of chestnut bee pollen against carbon tetrachloride (CCI4)-induced liver damage. Total phenolic content, flavonoid, ferric reducing/antioxidant power, and DPPH radical activity measurements were used as antioxidant capacity determinants of the pollen. The study was conducted in rats as seven gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…In general terms, since honey is a good antimicrobial mixture it is used in the treatment of various wounds and burns 39 . The antimicrobial features of honey are caused by factors such as acidity, osmolarity, H 2 O 2 , and secondary compounds 12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general terms, since honey is a good antimicrobial mixture it is used in the treatment of various wounds and burns 39 . The antimicrobial features of honey are caused by factors such as acidity, osmolarity, H 2 O 2 , and secondary compounds 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The many active biological properties of honey, which vary depending on the type of honey, such as its antioxidant, anti-inflammatory, immunomodulator, antiviral, antimicrobial and antitumor activities, are thought to derive from differences in these components 8,9 . Previous studies about chestnut honeys have showed that the honey have important antioxidant 10 , antimicrobial 11 , antihepatoprotective 12 , immunomodulator 6 and antitumoral 13 properties, which is reported to possess high levels of apitherapeutic and biologically active properties. And also, the chestnut honey contained a valuable among of phenolic substances that were responsible for its biological active features 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The great majority of these compounds that give rise to the true quality of honey are phenolic structure molecules, phenolic acids, flavanols, pro-anthocyanins and tannins that determine the aroma, taste and sensory characteristics of honey 34,35 . These secondary metabolites possess not only anti-oxidant activities, but also anti-microbial, anti-tumoral, and anti-inflammatory functions [36][37][38] . yCorrelation is significant at the 0.01 level (two-tailed).…”
Section: Resultsmentioning
confidence: 99%
“…However, when it was administered with toxic substances, it protected liver cells from their harmful effect, which indicates, in turn, its ability to prevent toxication. In the detoxifying process, an important role is played by polyphenols, mainly flavonoids and phenolic acids [28][29][30][31].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%